The Effect of “Everyone is A Teacher Here Learning” Model on the Critical Thinking Abilities at Grade IV Students on Civic Education Learning at UPTD SD Negeri 091263 Karangsari - Herlina Harefa; Minar Trisnawati L. Tobing; Imelda Sabrina Sibarani (International Journal of Technology and Education Research, 2026)
This study aims to determine the effect of the Everyone Is a Teacher Here learning model on the critical thinking skills of fourth-grade students in Civic Education (PKN) learning on rights and obligations at the UPTD of SD Negeri 091263 Karangsari. The background of this study is based on the low critical thinking skills of students as indicated by the results of initial observations, where as many as 60% of students have not achieved learning mastery. The low critical thinking skills are caused by learning that is still centered on the teacher and the use of less varied learning models. This study uses a quantitative approach with an experimental method and a one-group pretest-posttest design. The population and sample in this study were all fourth-grade students of UPTD SD Negeri 091263 Karangsari, totaling 25 people. Data collection techniques were carried out through pretest and posttest in the form of essay questions totaling 10 items that have been validated using the Aiken's V scale. The data analysis technique used was the N-Gain test and hypothesis testing using the t-test. The results showed that the application of the Everyone Is a Teacher Here learning model had a positive influence on students' critical thinking skills. This is demonstrated by the improvement in student learning outcomes after being treated with this learning model. The "Everyone Is a Teacher Here" model was able to increase students' active participation, their ability to ask questions, answer questions, express opinions, and draw conclusions during the learning process.